Analysis of the value of folk music intangible cultural heritage on the regulation of mental health - Ning, Hui (Frontiers in Psychiatry, 2023)
This paper proposes an approach based on the safeguarding of intangible cultural heritage (ICH) by studying the value of ICH to explore the value of the ICH of folk music on mental health and its safeguarding measures. Additionally, a questionnaire survey is conducted on the value of the ICH of folk music among college students. The Tibetan Guozhuang dance and music in the ICH are taken as the object. The students' awareness, participation, and effects on physical and mental health, emotional regulation, and stress regulation are investigated, to study the safeguarding value of folk music. The survey results reveal that in the process of participating in the folk art of Tibetan Guozhuang dance, 41.8% of the students consider it very useful for emotional regulation and stress relief, and 46.31% believe it is useful. 36.95% of the students feel that it is very useful for the development of mental health, and 49.75% think it is useful. This indicates that a total of 86.7% of the students believe that the dance is helpful to the development of students' mental health. And most of the students are in a happy mood when participating in the dance. Among them, 71.7% of the students say that they are elated, and 66.98% feel that they are excited. It illustrates that as a young group, the students are fond of folk art, but they lack the cognitive approach. Finally, the safeguarding suggestions and implementation paths are put forward in view of the existing problems of the ICH of folk music. The research can provide a research reference for the safeguarding of the ICH of folk music.